Occurrence and multidrug resistance of Campylobacter spp. at duck farms and associated environmental and anthropogenic risk factors in Bangladesh - Md. Nasir Uddin; Sucharit Basu Neogi; Sk Shaheenur Islam; Jannatul Ferdous; Md. Shahidur Rahman Khan; Shinji Yamasaki; S. M. Lutful Kabir (BMC Infectious Diseases, 2021)
Abstract Background The alarming rise in multi-drug resistant (MDR) zoonotic pathogens, including Campylobacter spp., has been threatening the health sector globally. In Bangladesh, despite rapid growth in poultry sector little is known about the potential risks of zoonotic pathogens in homestead duck flocks. The aim of this study was to understand the occurrence, species diversity, and multi-drug resistance in Campylobacter spp., and identify the associated risk factors in duck farms in Bangladesh. Methods The study involved 20 duck farms at 6 sub-districts of Mymensingh, Bangladesh. Monthly occurrence of Campylobacter spp. in potential sources at the farms during February-September, 2018, was detected by culture and PCR-based methods. Campylobacter isolates were examined for resistance to different antimicrobials. Risk factors, concerning climatic and environmental disposition, farm management, and anthropogenic practices, of Campylobacter infection were estimated by participatory epidemiological tools. Results Occurrence of Campylobacter spp. was detected in overall 36.90% (155/420) samples, more frequently in drinking water (60%, 30/50), followed by cloacal swab (37.50%, 75/200), egg surface swab (35%, 35/100) and soil of the duck resting places (30%, 15/50) but was not detected in feed samples (n = 20). PCR assays distinguished the majority (61.30%, 95/155) of the isolates as C. coli, while the rest (38.70%, 60/155) were C. jejuni. Notably, 41.7% (25/60) and 31.6% (30/95) strains of C. jejuni and C. coli, respectively, were observed to be MDR. The dynamics of Campylobacter spp., distinctly showing higher abundance during summer and late-monsoon, correlated significantly with temperature, humidity, and rainfall, while sunshine hours had a negative influence. Anthropogenic management-related factors, including, inadequate hygiene practices, use of untreated river water, wet duck shed, flock age (1–6 months), and unscrupulous use of antimicrobials were identified to enhance the risk of MDR Campylobacter infection. Conclusion The present study clearly demonstrates that duck farms contribute to the enhanced occurrence and spread of potentially pathogenic and MDR C. coli and C. jejuni strains and the bacterial dynamics are governed by a combined interaction of environmental and anthropogenic factors. A long-term holistic research at the environment-animal-human interface would be integral to divulge health risk reduction approaches tackling the spread of Campylobacter spp. from duck farms.